Kesadaran Hukum Masyarakat Pesisir Terhadap Pengelolaan Lingkungan di Desa Bukit Samang Kecamatan Sendana - Baharuddin, Wahdaniah; Dyastuti, Risqi Mumpuni (Programs Study Outside the Main Campus in Law Pattimura University ARU Islands Regency, 2023)
Environmental problems involve all components of the country and all elements of Indonesian society and even become rights and obligations, as regulated in Law Number 32 of 2009 concerning Environmental Protection and Management. Community participation, especially houses living in coastal areas, is very necessary in preparing plans for environmental management in the region. However, based on observations made by the author, the environmental conditions in the coastal area of ​​Bukit Samang, Sendana District, Majene Regency are included in the category of areas that are less clean. Traders who sell young coconuts along the beach still throw rubbish carelessly, potentially damaging the environment and polluting the coastal area. This research aims to determine the legal awareness of coastal communities regarding environmental management in Bukit Samang Village, Sendana District. This research is normative legal research. The approach is taken by reviewing literature or literature studies and directly observing conditions in the field related to the problem to be researched. The sources of legal materials used are primary and secondary legal materials which are then interpreted and analyzed qualitatively. Results of the research, this shows that The coastal area in Bukit Samang, Sendana District, Majene Regency is included in the category of areas that are less clean. This is characterized by a lack of legal awareness among the public or traders selling young coconuts along the coast who still throw rubbish carelessly which has the potential to damage the environment and pollute the coastal area. This is due to the government's unequal attention to areas far from the center of government, such as equal distribution of rubbish bins, in addition to providing sanctions that are only administrative in nature and do not have a deterrent effect on violators of space use.